Review of Software Testing Methods - Yasmin Makki Mohialden; Nadia Mahmood Hussien; Sundos Abdulameer Hameed (Newinera Publisher, 2022)
With the increasing complexity of programs comes an increased focus on ensuring the quality of these programs. Essentially, it depends on improving the methods of testing the quality of these programs in the two phases of building these programs and after their operation. Therefore, we are developing software testing methods and methodologies. This paper aims to discuss software testing methods and their classifications according to their main properties and any software that suits each method. The majority of the literature on software testing methods and techniques is also included.